An examination of the long-term business value of investments in information technology - Shea, Vincent J.; Dow, Kevin E.; Chong, Alain Yee-Loong; Ngai, Eric W. T. (Springer, 2017)
In this paper, we examine the effects of investments in Information Technology (IT) on the long term business values of organizations. The regression discontinuity design is used in this research to examine eight hundred and ten IT investment announcements collected from the period 1982–2007. Our results found that press releases can affect the market value of a firm by possibly providing investors with a better idea of a firm’s current and future operations and strategy. On the other hand, these press releases also appear to attract more transient investors. The attraction of transient investors likely suggests the market believes the IT investing firm is serious about its potential for growth and expansion.